Sulfur infiltration and allotrope formation in porous cathode hosts for lithium‐sulfur batteries. Issue 7 (18th February 2022) - Grabe, Sean; Baboo, Joseph Paul; Tennison, Stephen; Zhang, Teng; Lekakou, Constantina; Andritsos, Eleftherios I.; Cai, Qiong; Downes, Stephen; Hinder, Stephen; Watts, John F.
Abstract: We investigate sulfur infiltration and formation of lower order allotropes in heated porous hosts during fabrication of lithium‐sulfur (Li‐S) battery cathodes. Sulfur existence in cathode ultramicropores has been an important question for Li‐S batteries, as ultramicropores reduce the polysulfides "shuttle effect" but also delay sulfur dissolution and Li + ion diffusion in the trapped solid sulfur. A novel continuum‐level model is presented including heat transfer and sulfur infiltration, either from the top of a porous host or from the porous host particle surface, and taking into account the pore size distribution. A novel decay factor in modeling sulfur infiltration incorporates the pore wall repulsion energy and allotrope formation energy (predicted by density functional theory [DFT] simulations). Simulations are performed for a microporous carbon fabric host and an activated carbon powder host with bimodal micropore and macropore size distribution, with Raman and X‐ray photoemission spectroscopy (XPS) spectroscopy confirming the predicted existence of linear S6 and S4 in ultramicropores.